Monitoring population-level foraging distribution of a marine migratory species from land: strengths and weaknesses of the isotopic approach on the Northwest Atlantic loggerhead turtle aggregation - Simona A. Ceriani; Susan Murasko; David S. Addison; David Anderson; Greg Curry; Nicole A. Desjardin; Scott F. Eastman; Daniel R. Evans; Nancy Evou; Mariana M. P. B. Fuentes; Matthew H. Godfrey; Kristen M. Hart; et al. (Frontiers in Marine Science, 2023)
Assessing the linkage between breeding and non-breeding areas has important implications for understanding the fundamental biology of and conserving animal species. This is a challenging task for marine species, and in sea turtles a combination of stable isotope analysis (SIA) and satellite telemetry has been increasingly used. The Northwest Atlantic (NWA) loggerhead ( Caretta caretta ) Regional Management Unit, one of the largest sea turtle populations in the world, provides an excellent opportunity to investigate key biological patterns as well as methodological aspects related to the use of stable isotopes to infer spatial distribution of turtles in foraging areas. We provide the first comprehensive assessment of the annual distribution of NWA adult female loggerheads among foraging areas and investigate the efficacy of various analytical approaches as well as the effect of sample size in these types of studies. A total of 5168 individual females were sampled from seven Management Units (MUs) between 2013-2018. We provide the first estimate of the proportion of females originating from each MU that uses each foraging area and show how this proportion varies over time. We also estimate the relative importance (in terms of number of turtles) of each foraging area to the overall loggerhead breeding aggregation nesting in Florida and in the NWA for each year of the study. The foraging area used by reproductively active females differs considerably across MUs. One of these, the Subtropical NWA, is by far the most important foraging area in terms of both number of individuals and genetic diversity, and therefore this region may be considered as a conservation priority. Through simulations, we show that limited sizes of sample groups (unknowns; training; priors) may result in false geographic differentiation and consequently mislead interpretations. We provide thresholds and methodological recommendations for future studies. This study establishes a fundamental baseline for monitoring the annual contribution of foraging area to a terrestrial-based breeding aggregation of a marine animal in a cost-effective way. This type of monitoring allows for early detection of changes in foraging distributions—a possible effect of climate change on marine ecosystems or of area-specific anthropogenic threats.

Genotoxicity evaluation of cannabidiol - Rayetta G. Henderson; Brian T. Welsh; Kristen R. Trexler; Marcel O. Bonn-Miller; Timothy W. Lefever (Regulatory Toxicology and Pharmacology, 2023)

Reproductive and developmental toxicity evaluation of cannabidiol - Rayetta G. Henderson; Brian T. Welsh; John M. Rogers; Susan J. Borghoff; Kristen R. Trexler; Marcel O. Bonn-Miller; Timothy W. Lefever (Food and Chemical Toxicology, 2023)

Vision-based model updating and evaluation of miter gates on inland waterways - Shuo Wang; Casey Rodgers; Travis Fillmore; Brian Welsh; Thomas Golecki; Shaik Althaf V. Shajihan; Brian A. Eick; Billie F. Spencer (Engineering Structures, 2023)

Motor variability: within-subject correlations during separate and simultaneous contractions - Brian L. Tracy; Devin V. Dinenno; Bjørn Jørgensen; Seth J. Welsh (Experimental Brain Research, 2008)

Variability of quadriceps femoris motor neuron discharge and muscle force in human aging - Seth J. Welsh; Devin V. Dinenno; Brian L. Tracy (Experimental Brain Research, 2007)